Performance improvements of microchannel heat sink using wavy channel and nanofluids - Sakanova, Assel (2015)
To improve the heat transfer performances of microchannel heat sink (MCHS), the advanced channel structures and working fluids can be applied. In this paper, the wavy channel structure and application of nanofluids are investigated. The effects of wavy amplitude, wavelength, volumetric flow rate and volume fraction of different type of nanofluids are presented. Three wave amplitudes of 25 μm, 50 μm and 75 μm with two wavelength of 250 μm and 500 μm at volumetric flow rate ranges from 0.152 L/min to 0.354 L/min are considered. Three different types of nanofluids with volume concentration ranges from 1% to 5% are applied. The effect of wavy MCHS is shown on thermal resistance, pressure drop, friction factor. It is found that in case of the pure water is applied as the coolant the heat transfer performance of the MCHS is significantly improved comparing with the traditional straight channel MCHS, while the replacement of the pure water by nanofluids makes the effect of wavy wall unnoticeable.